Complete Uterine Prolapse in a Cat - Binli, Firdevs; Büyükbudak, Fatih; İnan, İpek; Fındık, Murat; Ay, Serhan Serhat; Binli, Firdevs; Buyukbudak, Fatih; Inan, Ipek; Findik, Murat; Ay, Serhan Serhat (Ankara Univ Press, 2021)
In this case, it was presented a case of complete uterine prolapse in a cat following a third parturition at the age of 18 months. Upon physical examination complete uterine prolapse was diagnosed due to a mass protruding from the vulva which included both uterine horns. After the invagination and eversion were corrected and the uterus was relocated to its anatomical position, ovariohysterectomy was performed. Sutures were removed ten days after the operation. Following shrinking of uterus by using the hypertonic fluid and repositioning, ovariohysterectomy is a suitable and reliable option for cats with complete uterine prolapse.
Bir Kedide Tam Uterus Prolapsusu
Q4
Findik, Murat/0000-0003-1408-2548; Ay, Serhan Serhat/0000-0003-2116-5149;
Keywords: Cat; Ovariohysterectomy; Parturition; Uterine Prolapse; Veterinary Sciences